BUSINESS PLAN FOR OPENING AN ONLINE STORE SELLING UNIQUE BABY CLOTHES - SO CUTE! WITH EMPHASIS ON ONLINE MARKETING - Martins, Carla Fernanda; Machado, Luís Eduardo (Seven Editora, 2025)
This work aims to expand upon and address the principles of customer-centric marketing in a competitive environment and commercial management. Through literature on the subject, it seeks to convey some basic concepts, focusing on the dynamic changes occurring in marketing in a globalized world. It focuses on developing and integrating the idea of ​​creating value for customers as the primary goal of marketing, helping to understand its principles and how its elements are used to create value for customers and achieve organizational objectives for effective management in the commercial area. In the context of online stores, according to the developed management PIN, it applies viable fundamentals to meet this demand.DOI: https://doi.org/10.56238/sevened2025.036-070